NAVIGASI KESUKSESAN GURU DAN SISWA DI SEKOLAH DASAR DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA - Rifa’i, Ahmad Iqbal; Putra, Naufal Diama (Abtadi : Jurnal Pendidikan Dasar, 2024)
ABSTRACT: The Merdeka curriculum is a student-centered curriculum aimed at promoting critical thinking, creativity, and problem-solving skills among students, it emphasizes the importance of holistic education, which combines not only academic subjects but also socio-emotional learning and practical skills. One aspect of the Merdeka Curriculum is to emphasize personalized learning to meet the individual needs of students and increase their involvement in the learning process. To create successful learning in an independent curriculum, it is necessary to discuss the implementation, navigation of success, challenges, and impact of the Merdeka Curriculum in Indonesian primary schools, with a focus on the experience of teachers and students. This research uses a qualitative approach with a library study as a data collection method. Merdeka's curriculum has improved student engagement, creativity, and problem-solving skills despite challenges such as adaptation of new teaching methods and technologyintegration. The teachers found that collaboration and professional development continuously supported successful implementation. It is also about strategies for the successful navigation of teachers and students in the Free Curriculum, including inclusive practices and the necessary support system to support educators in improving the quality of education for all students, by adapting teaching methods and creating an inclusive and supportive learning environment.